2010
DOI: 10.1177/0961203310366573
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus is an alternative therapeutic option for the treatment of refractory lupus nephritis

Abstract: We conducted an open-labeled, prospective study to determine the efficacy and safety of tacrolimus as an alternative therapeutic option for those patients with refractory lupus nephritis. The study population comprised one male and eight female patients with diffuse proliferative lupus nephritis. All patients had failed to respond to sufficient intravenous cyclophosphamide therapy with proteinuria of >or=1 g/day and active urinary sediments. Tacrolimus (0.1 mg/kg/day) was administered for 1 year with adjusting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…Several papers have reported the efficacy and absence of serious adverse effects of Tac plus PDN when administered as induction and maintenance therapy for patients with proliferative and membranous LN [7,12,13,14,15,16,17,18,19,20]. Each of these studies described the need for aggressive cytotoxic therapy to induce remission of LN; however, long-term cytotoxic therapy can have serious side effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several papers have reported the efficacy and absence of serious adverse effects of Tac plus PDN when administered as induction and maintenance therapy for patients with proliferative and membranous LN [7,12,13,14,15,16,17,18,19,20]. Each of these studies described the need for aggressive cytotoxic therapy to induce remission of LN; however, long-term cytotoxic therapy can have serious side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these studies described the need for aggressive cytotoxic therapy to induce remission of LN; however, long-term cytotoxic therapy can have serious side effects. In this context, Tac has been reported to be an alternative treatment option to IVCY or MMF for patients with LN, although calcineurin inhibitor-related nephrotoxicity remains a major concern [7,12,13,14,15,16,17,18,19,20]. Recently, Chen et al [19] reported the short-term efficacy and safety of Tac compared with IVCY for induction therapy in patients with active LN (ISN/RPS class III, IV and V).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant reduction of proteinuria was observed at 3 months and 12 (70%) patients achieved clinical response after a 2-year follow-up. In a pilot study, Mok et al demonstrated the safety and efficacy of tacrolimus when used (39). Tacrolimus (0.1 mg/kg per day) was administered for 1 year.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%